Fracture behavior of single crystal silicon with thermal oxide layer. (September 2016) - Tsuchiya, Toshiyuki; Miyamoto, Kenji; Sugano, Koji; Tabata, Osamu
Highlights: Tensile testing on oxidized single crystal silicon beams was conducted. Electrostatic grip was used for tensile-testing of cantilever silicon specimens. Fracture origin locations changed by oxidation and thickening oxide layer. Oxygen precipitations became fracture origin of 200 nm thick oxidized silicon. Abstract: This paper reports on the effect of oxidation on fracture behavior of single crystal silicon (SCS). SCS specimens were fabricated from (1 0 0) silicon-on-insulator wafer with 5-μm-thick device layer and oxide layer were thermally grown. Quasi-static tensile testing of as-fabricated, oxidized and oxidized layer removed specimens was performed. The fracture origin location transited from the surface to silicon/oxide interface and inside of silicon. The transition may be caused by surface smoothing, thickening oxide layer and formation of oxide precipitation defects in silicon during oxidation. The radius of the oxide precipitation defects was estimated, which is well agreed with the fracture-initiating crack sizes.